PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING TERHADAP KREATIVITAS BELAJAR DAN HASIL BELAJAR SISWA KELAS XI TEKNIK KOMPUTER JARINGAN SMK NEGERI 1 NABIRE POKOK BAHASAN GETARAN DAN GELOMBANG - MUSTIKA IRIANTI (Jurnal Ilmu Pendidikan Indonesia, 2018)
This Research aims to understand the impact of problem posing learning model (X) towards learning creativity (Y1) and result (Y2) of XI grade students of computer and network engineering 3 at SMK Negeri 1 Nabire.This qualitative research applies purposive sampling technique which involved 25 students. The obtained pre-test and post-test data were used to understand the students learning result and questionnaire data for students learning creativity. (1) There is significant impact of problem posing learning model towards learning creativity of XI grade students of computer and network engineering 3 at SMK Negeri 1 Nabire with the discussion on vibration and wave ; (2) There is significant impact of problem posing learning model towards the learning result of XI grade students of computer and network engineering 3 at SMK Negeri 1 Nabire with the discussion on vibration and wave that is showed by t-test as 0,003 (0,003 < 0,05) ; (3) there is increasing value on learning result of XI grade students of computer and network engineering 3 at SMK Negeri 1 Nabire with the discussion on vibration and wave  that is show by n-Gain as 0,76 which can be categorized as high result.